Fabrication of graphene and graphene-based electrode for electroanalysis - Lua, Shu Qi. (2011)
The focus of this report will be on the identification, fabrication and testing of a nano-material which is sensitive to single atoms or molecules in order to create an ideal detector. The nano-material will then be used as a working electrode to carry out electro-analysis. By evaluation and theoretical analysis from publications and actual testing, the nano-material will be evaluated of its properties and feasibility as an ideal detector.